2012
DOI: 10.1364/oe.20.006340
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic effects in amorphous silicon thin film solar cells with metal back contacts

Abstract: Plasmonic effects in amorphous silicon thin film solar cells with randomly textured metal back contact were investigated experimentally and numerically. The influence of different metal back contacts with and without ZnO interlayer was studied and losses in the individual layers of the solar cell were quantified. The amorphous silicon thin film solar cells were prepared on randomly textured substrates using large area production equipment and exhibit conversion efficiencies approaching 10%. The optical wave pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 18 publications
1
48
0
Order By: Relevance
“…For all three metals, the absorption pattern shows a strong blue shift when the refractive index of the embedding medium is reduced (going from a-Si:H to SiO x :H and finally to ZnO:Al). This is in agreement with the results presented by Palanchoke et al, 20 who observed that an additional ZnO interlayer between the silicon solar cell and the metal back contact causes a shift of the localised plasmon resonances to shorter wavelengths. The wavelength range that is relevant for light trapping in a-Si:H solar cells is indicated in Fig.…”
Section: Discussionsupporting
confidence: 93%
“…For all three metals, the absorption pattern shows a strong blue shift when the refractive index of the embedding medium is reduced (going from a-Si:H to SiO x :H and finally to ZnO:Al). This is in agreement with the results presented by Palanchoke et al, 20 who observed that an additional ZnO interlayer between the silicon solar cell and the metal back contact causes a shift of the localised plasmon resonances to shorter wavelengths. The wavelength range that is relevant for light trapping in a-Si:H solar cells is indicated in Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Likewise, we considered a pyramid which has a consistent opening edge of 120°. All through the examination, FDTD strategy in three dimensions (3D) was utilized to mimic the solar cell investigating the optical wave spread and compute the losses in the individual layers (Palanchoke et al 2012;Huang et al 2013;Tamang et al 2016c).…”
Section: Design and Optical Modelmentioning
confidence: 99%
“…The time standard power loss can be figured utilizing the following equation (Palanchoke et al 2012):…”
Section: Solar Cell With Smooth Substratementioning
confidence: 99%
See 1 more Smart Citation
“…Such texturing requires micron-size features that are inapplicable to novel, flexible thin-film solar cells whose active area is thinner than one micrometer. Introducing small-scale plasmonic structures at the back surface of the solar cell has also produced efficiency improvements, 2 but these structures may be difficult to introduce into flexible thin films manufactured on a large-area plastic substrate, especially if high temperatures are required during the process of depositing the plasmonic structures and/or the thin photovoltaic film whose efficiency requires enhancement.…”
Section: Introductionmentioning
confidence: 99%